Changes in Cross-Sectional Area and Signal Intensity of Healing ACLs and ACL Grafts in the First Two Years After Surgery - Kiapour, Ata M. (Am J Sports Med, 2019)
BACKGROUND: The quality of a repaired anterior cruciate ligament (ACL) or reconstructed graft is typically quantified in clinical studies by evaluating knee, lower extremity or subject performance. However, magnetic resonance (MR) imaging of the healing ACL or graft may provide a more direct measure of the tissue quality (i.e., signal intensity) and quantity (i.e., cross-sectional area). HYPOTHESIS: 1) Average cross-sectional area or signal intensity of a healing ACL following Bridge-Enhanced ACL Repair (BEAR) of a midsubstance ACL tear or a hamstring autograft (ACLR) will change postoperatively from 3 to 24 months. 2) The average cross-sectional area and signal intensity of the healing ligament or graft will correlate with anatomical features of the knee associated with ACL injury. STUDY DESIGN: Cohort Study; Level of evidence, 2. METHODS: Subjects with a complete, midsubstance ACL tear who were treated with either BEAR (n=10) or ACLR (n=10) underwent MR imaging at 3, 6, 12 & 24 months after surgery. Images were analyzed to determine the average cross-sectional area and signal intensity of the ACL or graft at each time point. ACL orientation, stump length and bony anatomy were also assessed. RESULTS: Mean cross-sectional area of the grafts was 48–98% larger than the contralateral intact ACL at all time points (p<.01). The BEAR ACLs were 23–28% greater than the contralateral intact ACL at 3 and 6 months (p<.02), but similar at 12 and 24 months. The BEAR ACLs were similar in sagittal orientation to the contralateral ACL while the grafts were 6.5° more vertical (p=.005). For the BEAR ACLs, the bigger notch correlated with bigger cross-sectional area, while a shorter ACL femoral stump, steeper lateral tibial slope and shallower medial tibial depth were associated with higher signal intensity (R(2)>.40; p<.05). Performance of notchplasty resulted in increased ACL cross-sectional area after the BEAR procedure (p=.007). No anatomic features were correlated with ACL graft size or signal intensity. CONCLUSIONS: Hamstring autografts were larger in cross-sectional area and more vertically oriented than the native ACL at 24 months after surgery. BEAR ACLs have a cross-sectional area, signal intensity and sagittal orientation that were similar to the contralateral ACL at 24 months. The early signal intensity and cross-sectional area of the repaired ACL may be affected by specific anatomic features, including lateral tibial slope and notch width, observations that deserve further study in a larger cohort of subjects.